2002
DOI: 10.1080/03091900210156896
|View full text |Cite
|
Sign up to set email alerts
|

A methodological approach for the characterization of cardiac pacemaker immunity to low frequency interferences: case of 50 Hz, 60 Hz, 10 kHz and 25 kHz led disruptions

Abstract: The goal of this work is the implementation of a metrological set up dedicated to the characterization of cardiac pacemakers' immunity at low frequency electromagnetic disruptions. The studied frequencies are 50 Hz, 60 Hz, 10 kHz and 25 kHz. The assessment methodology that is applied is in accord with the electromagnetic compatibility. The tests are carried out on single-chamber pacemakers. The first approach, consisting of the application of the interfering signal directly between the housing and the electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…These studies are discussed in detail in the ‘Phantom Studies—Coupling Model’ section. Nevertheless, due to the data of these studies it can be summarized that the lowest detection levels were found from 55 mV (10 kHz) 62 and 95 mV (25 kHz) 64 depending on the sensitivity level of the PM 64 . Comparable detection levels were also found in an earlier study by the same research group 39 combining benchmark tests and phantom investigations.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…These studies are discussed in detail in the ‘Phantom Studies—Coupling Model’ section. Nevertheless, due to the data of these studies it can be summarized that the lowest detection levels were found from 55 mV (10 kHz) 62 and 95 mV (25 kHz) 64 depending on the sensitivity level of the PM 64 . Comparable detection levels were also found in an earlier study by the same research group 39 combining benchmark tests and phantom investigations.…”
Section: Resultsmentioning
confidence: 48%
“…Hedjiedj et al 62 developed a transfer function based on a simple phantom and found detection levels from >55/104 mV at 10/25 kHz for a sensitivity level of 0.7 mV. The authors also included benchmark tests and reported detection levels in two out of five PMs of >150/130 mV at 10/25 kHz for a sensitivity level of 1 mV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two questions have been the subject of several studies over the last decades, in vivo and in vitro. A. Hedjeidj et al in 2002 showed that the exposure of certain PCs to NDEs under specific conditions caused their dysfunction [4]. J Silny et al, in 2014 they showed after the exposure of 110 patients (worn ICDs of 1,2, and 3 chamber) to strong electric and magnetic fields of 50 Hz ranging up to 30kv / m, and 2.55 mT in some work environments may cause inappropriate detection, which may lead to false detection of atrial/ventricular arrhythmic events [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on lowfrequency electromagnetic fields as a cause of interference are rare, and mainly restricted to a power frequency of 50/60 Hz [15][16][17][18][19][20][21][22] or to frequencies of some specific device, such as an induction oven [23][24][25]. Studies carried out using Helmholtz coil systems are usually restricted to sinusoidal and pulse waveforms.…”
Section: Introductionmentioning
confidence: 99%